Colorectal carcinoma in Sudanese patients - Mohammed, Mutaz; Musaad, Abd elmagid; Eltayeb, Elsaggad; A elaziz, Muataz (International Journal of Medicine, 2015)
Background: Cancer is an increasingly important public health problem in developing countries, including Sudan. The burden of colorectal cancer in Sudan is unknown, mainly because of lack of statistics or under reporting. Colorectal carcinoma is the most common malignancy of the GI tract, unfortunately there are few statistical data regarding colorectal cancer, its geographical, ethnic distribution, & pattern of behavior in Sudan.Objective: To assess pattern of presentation, management, & postoperative complication of colorectal carcinoma patients who presented to Ibn Sina hospital.Patients and method: This is a descriptive study between (2012-2014); a prospective & retrospective study of histological confirmed cases of colorectal cancer was conducted at Ibn Sina hospital.Result: Sixty three patients were included within the study. The mean age of the patients was 50.5 (Â±11.7). The median duration until presentation was 10 months. Left-side colonic carcinoma was 81% represented the majority of cases with Rectosigmoid cancer account for 74% of all cases. The most common presenting symptoms were alteration of bowel habits 90.5% and rectal bleeding 84%. Anemia was reported in 62.5% of right side colonic carcinoma while only in 23.5% of left colonic carcinoma. CEA was found positive in 85.3% (n=35). Postoperative morbidity in this study was 38%. All tumors were adenocarcinoma, and 65% of the sample were advanced â€œDuke's stage C & D."Conclusion: A younger age group with late presentation and advance disease, making the possibility of cure difficult if we take into consideration the scarcity of the resources.